A Critical Study on Impact of Demonetization on Industrial Sector of Indian Economy - . Kapoor, .B; Kumar Maurya, Santosh (International Journal of Psychosocial Rehabilitation, 2019)
Demonetisation is the withdrawal of units of cash from circulation; units of cash are refused legal tender status. Demonetisation is described as a method that does not allow currency units to stay a legal tender. It will not take the currency notes as valid currency. Demonetisation is a move made by the government to cease its status as a legal tender for currency units. It will not take the currency notes as valid currency. Demonetisation is a move made by the government to cease its status as a legal tender for currency units. Demonetisation is a fundamental prerequisite for changing national currency. In other words, a shift of currency can be called demonetisation, where fresh currency units substitute the old one. It may require fresh notes or coins being introduced same denomination or entirely new denomination. In India, the currency was demonized three times. The first demonization took place on January 12, 1946 (Saturday), the second on January 16, 1978 (Monday) and the third on November 8, 2016 (Tuesday). The research tries to comprehend the significance and reasons of demonetisation, the wise effect of demonetisation on the industry. Same denomination or completely new denomination. In India, three times the currency has been demonized. On January 12, 1946, on January 16, 1978, and on November 8, 2016, the first demonization took place. The study attempts to understand the importance and reasons of demonetisation, the wise impact on the sector of demonetisation. This study is also being done.